Demographic and clinical features of neuromyelitis optica: A review. (June 2015) - Pandit, L; Asgari, N; Apiwattanakul, M; Palace, J; Paul, F; Leite, MI; Kleiter, I; Chitnis, T; ,
The comparative clinical and demographic features of neuromyelitis optica (NMO) are not well known. In this review we analyzed peer-reviewed publications for incidence and prevalence, clinical phenotypes, and demographic features of NMO. Population-based studies from Europe, South East and Southern Asia, the Caribbean, and Cuba suggest that the incidence and prevalence of NMO ranges from 0.05–0.4 and 0.52–4.4 per 100, 000, respectively. Mean age at onset (32.6–45.7) and median time to first relapse (8–12 months) was similar. Most studies reported an excess of disease in women and a relapsing course, particularly in anti-aquaporin 4 antibody (anti AQP4-IgG)-positive patients. Ethnicity may have a bearing on disease phenotype and clinical outcome. Despite limitations inherent to the review process, themes noted in clinical and demographic features of NMO among different populations promote a more global understanding of NMO and strategies to address it.